PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI SD INPRES 2 DESA GIO KECAMATAN MOUTONG KABUPATEN PARIGI MOUTONG - Tasrif, Risna; Gusnarib; M, Masmur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of the principal in improving teachers' pedagogical competence at SD Inpres 2 Desa Gio, Moutong District, Parigi Moutong Regency, and identifies its supporting and inhibiting factors. This study employed a descriptive qualitative approach. Data collection techniques included observation, interviews, and documentation. The collected data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that the principal has implemented seven main roles, namely as an educator, manager, administrator, supervisor, leader, innovator, and motivator. Among these roles, the role of supervisor is the most dominant in improving teachers' pedagogical competence. The implementation of this role has a positive impact on enhancing teachers' abilities in understanding learners' characteristics, mastering learning theories, developing curriculum, and implementing learning assessment and evaluation. Supporting factors include the availability of digital facilities and infrastructure. Meanwhile, inhibiting factors include internet connection instability and teachers' heavy administrative workloads. This study concludes that strengthening supervision combined with the utilization of technology can significantly accelerate the improvement of teachers' pedagogical quality.